Wetland Dynamics Using Geo-Spatial Technology - Das N.; Ohri A.; Agnihotri A.K.; Omar P.J.; Mishra S. (My University, 2025)
Wetlands are very significant part of our environment. They improve water quality of its area and also makes local climate fairly moderate. Among the fertile areas of environment system, wetlands are the one. As the wetland decreases, it brings changes to weather pattern and diminution of water level below soil. Like many wetlands in India, wetland of Varanasi district is also facing with danger and diminishing day by day. Due to the rapid increase in urbanization of the city and population explosion over the last two decades, the encroachment process is taking place at a brisk rate; therefore, wetland area is reducing accordingly. So objective of this work is the mapping of wetland area in Varanasi district with the help of remote sensing using multi-date Landsat satellite data for two particular years 1990 and 2016. Water pixels have been demarcated by using Normalized Difference Water Index (NDWI). In the result of the study, it has been found that wetland area’s reduction has been around 43% for the period spanning around 26 years. This is a cause of great concern that wetland area is reducing at a very fast rate; therefore, it is urgent need to protect these wetland area as this is one of the major components for sustaining balance in our ecosystem. © 2020, Springer Nature Singapore Pte Ltd.